Kidney and Ileum Histopathology of Rattus norvegicus Toxicity Model of Rhodamine B and Saccharin Supplemented with Purple Roselle Yoghurt - Dzakiyyah Salmaa; Ajeng Erika Prihastuti Haskito; Anna Safitri; Aldila Noviatri; Handayu Untari; Citra Sari (Journal of Applied Veterinary Science and Technology)
Background: Rhodamin B and saccharin are chemicals that are harmful to the health of the body. Consumption of rhodamine B and saccharin for a long time can cause problems for the body such as impaired organ function. Purpose: The aim was to find out the benefits of giving purple rosella yogurt in preventing damage to the kidneys and ileum of Rattus norvegicus caused by rhodamine B and saccharin. Methods: Using RAL with 28 male Rattus novergicus aged 8-12 weeks. Group K(-) was not given any treatment, K(+R) was given rhodamine B, K(+S) was given saccharin, K(+K) was given rhodamine B and saccharin, P1 was given rhodamine B and yoghurt, P2 was given saccharin and yoghurt, P3 was given rhodamine B, saccharin, and yogurt. The dose of rhodamine B was 22.5 mg/kg, the dose of saccharin was 157.7 mg/kg, the volume of yoghurt was 1 ml/head. Administered orally with gastric tube for 14 days. The concentration of purple rosella extract used was 15% (v/v). Results: Group K(+K) showed the heaviest damage. Groups P1, P2, and P3 still found damage to the kidneys, in P1 they experienced thickening of Bowman's capsule in the glomerulus, in P2 they experienced a loss of more than 25% of the brush border in the tubules, and in P3 they experienced glomerular tufts in the glomerulus. In the ileum, P1 experienced thickening of the muscles, P2 experienced clusters of inflammatory cells in the submucosa, and P3 experienced 10-50% loss of goblet cells. Conclusion: Provision of purple rosella yogurt can prevent damage to the kidneys and ileum of Rattus novergicus due to rhodamine B and saccharin, although it is not optimal.